Possible molecular exploration of herbal pair Haizao-Kunbu in the treatment of Graves’ disease by network pharmacology, molecular docking, and molecular dynamic analysis - Yang, Mengfei; Lai, Yiwen; Gan, Di; Liu, Qingyang; Wang, Yingna; He, Xinyong; An, Yi; Gao, Tianshu (Frontiers in Endocrinology, 2023)
Objective: To better servepromote the development and therapeutic application of novelnew medications, it is requiredcrucial to comprehensively examineconduct a thorough investigation into the mechanism ofby which the typical traditional Chinese herb pair of Haizao-Kunbu (HK) treatingtreats Graves' disease (GD).Materials and methods: Chemical ingredients of HK, putative target genes, and GDassociated genes were collected in theretrieved from online public databases. Using Cytoscape 3.9.1, Aa compound-gene target network was established to illustrateexplore the association between prosperous ingredients and targets. STRING, Gene Ontology, and Kyoto Encyclopedia of Genes and Genomes pathway analyses visualized core targets and disease pathways. We further screened Additionally, we conducted a refined analysis of the binding situations amonginteractions between active ingredients withand their respective targets and visualized the data through. To visualize these findings, we employed precise molecular docking while we performedtechniques. Furthermore, we carried out molecular dynamics simulations to exploregain insights into the formation of more tightly combinedbound complexes. Results: It was finally determinedWe found that there were nine significantkey active substancesingredients in HK, which mainly actacted on 21 targets. These targets primarily regulated someseveral biological processes likesuch as cell population proliferation, protein phosphorylation, and regulation of kinase activity, with practical effectsand acted on the PI3K-AKT and MAPK pathways, playing a crucial part in treating to treat GD. The visualizationsAnalysis of the molecular interaction simulation under computer technology showedrevealed that the key targets have a highexhibited strong binding activity to active ingredients, and Fucosterol-AKT1 and Isofucosterol-AKT1 complexes were highly stable in humans.OurThis study founddemonstrates that HK may haveexerts therapeutic effects on GD in a multi-component, multi-target, and multi-pathway manner by regulating cell proliferation, differentiation, inflammation, and immunomodulatory-related targets, which. This study provides a theoretical foundation for further investigation into GD.